2003
DOI: 10.1124/jpet.103.057059
|View full text |Cite
|
Sign up to set email alerts
|

The Interleukin-1β-Converting Enzyme Inhibitor Pralnacasan Reduces Dextran Sulfate Sodium-Induced Murine Colitis and T Helper 1 T-Cell Activation

Abstract: The proinflammatory cytokines interleukin (IL)-1␤ and IL-18 are supposed to play a crucial role in the pathogenesis of human inflammatory bowel disease. To exert biological activity, the precursors of both IL-1␤ and IL-18 need to be cleaved by the interleukin-1␤-converting enzyme (ICE). IL-18 induces the synthesis of IFN-␥ in T cells and NK cells. In the present study, we investigated the effect of the specific ICE inhibitor pralnacasan in dextran sulfate sodium-induced murine colitis. Colitis was induced in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 27 publications
2
73
0
1
Order By: Relevance
“…Consistent with this, we found that infiltration of neutrophils and macrophages into the CNS during the development of EAE, which is driven by Th17 and Th1 cells, respectively, was attenuated by treatment with the caspase-1 inhibitor. Caspase-1 inhibitors have already shown efficacy in experimental models of multiple sclerosis, colitis, pancreatitis, and seizure (29,(31)(32)(33)(34). Pralnacasan, a caspase-1 inhibitor, has also shown some efficacy in phase II clinic trails in rheumatoid arthritis patients, but the trial was discontinued because of toxicity issues in long-term animal studies (35).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, we found that infiltration of neutrophils and macrophages into the CNS during the development of EAE, which is driven by Th17 and Th1 cells, respectively, was attenuated by treatment with the caspase-1 inhibitor. Caspase-1 inhibitors have already shown efficacy in experimental models of multiple sclerosis, colitis, pancreatitis, and seizure (29,(31)(32)(33)(34). Pralnacasan, a caspase-1 inhibitor, has also shown some efficacy in phase II clinic trails in rheumatoid arthritis patients, but the trial was discontinued because of toxicity issues in long-term animal studies (35).…”
Section: Discussionmentioning
confidence: 99%
“…Tissue levels of IL-8 have been reported to be upregulated in cases of CD and UC (37). IL-1␤ is crucial to IBD pathology, and its inhibition has been shown to attenuate DSS colitis through inhibition of proinflammatory activity and possibly downstream proangiogenic activity (91). IL-12 and IL-18 are inducers of IFN-␥ and TNF-␣ production in lymphocytes; however, observations in DSS colitis revealed that IL-12 Ϫ/Ϫ mice develop mild colitis whereas IL-18 Ϫ/Ϫ mice develop severe colitis, indicating that IL-12 may be more protective than IL-18 (152).…”
Section: Angiogenic Mediators In Ibd and Experimental Colitismentioning
confidence: 99%
“…Disorder of autoimmunity is closely related to the imbalance of Th 1 and Th 2 cells. For IFN-γ being on Th 1 cell, abnormal expressions of IFN-γ and IFN-γ mRNA cause inevitably the imbalance of Th 1 /Th 2 and result in immune disorder [38][39][40] . CD 11a + /CD 18 + are cell surface adhesive albumin, also known as lymphocyte function antigen-l (LFA-l), a representative of β 2 integrants.…”
Section: Discussionmentioning
confidence: 99%